Physiological quality of wheat seeds submitted to saline stress - Duarte,Gisela Loureiro (2006)
The objective of this experiment was to determine the influence of different salt levels (zero, 15, 30, 45 and 60mM NaCl) on seed physiological quality of two wheat cultivars (BRS 177 and BRS 179). SUMMARIZE METHODOLOGY. The results allow the following conclusions: the physiological quality (germination and vigor) of wheat seeds, cultivars BRS 179 and BRS 177, decrease with the increase of the salinity. The wheat seeds cv. BRS 179 performs better than BRS 177, mainly in higher salt concentrations (³ 45mM of NaCl). The electric conductivity of wheat seeds increases in function of the increment of the saline concentrations.